Quantitative analysis of degradation mechanisms in 30-year-old PV modules - Liu, Zhe; Castillo, Mariela Lizet; Youssef, Amanda; Serdy, James G.; Watts, Alliston; Schmid, Cordula; Kurtz, Sarah; Peters, Ian Marius; Buonassisi, Tonio (Solar Energy Materials and Solar Cells, 2019)
Quantitative analysis of two 30-year-old PV modules is performed by a combination of the equivalent-circuit model and optoelectronic characterization methods. The two modules under analysis were manufactured in 1984 with the nameplate power of 41.0 W, but degraded under two different conditions; one was operated in the field in Northern California for about 30 years, and the other was stored in a warehouse for the same period. The power outputs of the two modules measured in 2016 are as 28.4W for the field-exposed one and 35.9 W for the warehoused one. We further break down this power difference of 7.5 W ± 0.3 W to specific physical mechanisms. Through the encapsulant transmittance measurements and the circuit modeling of module I–V curves, the power degradation due to encapsulant discoloration is found as 59% ± 4% of the total difference. With the bias-dependent electroluminescence imaging and the dark I–V measurement of solar cells (via the additionally-attached probe wires), the series-resistance increase is attributed to 33% ± 1%, with the split of 13% ± 4% due to interconnection resistance and 20% ± 4% due to cell resistance. In addition, the synergistic effect of all the physical mechanisms makes up the remaining 8% ± 4%. This case study presents an example of analyzing multiple degradation mechanisms of the PV modules. With more characterization data being collected for today's modules, the same analysis framework can be broadly applied, yield great insights module power degradation attributed to multiple loss mechanisms.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Device characterization; Device modeling; Power loss analysis; PV module degradation; PV reliability